The attentional boost effect in individuals prone to depression: a Remember/Know analysis based on emotional valence and material type - Xie, Qinling; Zhang, Meina; Wang, Yiyuan; Wang, Di; Huang, Fajie (Frontiers in Psychiatry, 2025)
This study provides the first comprehensive investigation of the attentional boost effect (ABE) in individuals prone to depression under varying conditions of emotional valence and material type. It further examines whether ABE is driven primarily by enhanced recall of target information or by the inhibition of distractor processing. A four-factor mixed design (Group × Material Type × Emotional Valence × Stimulus Type) was employed with 60 university students (30 individuals prone to depression, 30 healthy controls). Participants completed a classical ABE paradigm combined with the Remember/Know (R/K) memory task to assess recognition performance and ABE effect sizes across conditions. The results revealed that: (1) both groups demonstrated significant ABE, supporting its cross-group robustness; (2) under the “positive–picture” condition, the ABE effect in the depression-prone group tended to be weaker than in healthy controls, suggesting a condition-specific attenuation under the interaction of emotion and material type; (3) ABE primarily emerged in Remember responses rather than Know responses, reflecting an advantage for conscious recollection of target stimuli, while the depression-prone group additionally exhibited “reversed ABE” in certain conditions, where distractors elicited greater familiarity; and (4) the modulatory roles of material type and emotional valence were stage-dependent, with picture stimuli—characterized by higher arousal—being more sensitive to emotional modulation, whereas word stimuli showed greater semantic stability. These findings suggest that although individuals prone to depression generally retain ABE, their conscious recollection of targets is selectively weakened under positive emotional contexts, accompanied by reduced efficiency in distractor inhibition. This study extends the applicability of ABE theory to subclinical populations and provides novel empirical evidence for understanding attention–memory coupling and depression-related cognitive biases.